Prosodic focus in English vs. French: A scope account. Issue 1 (15th June 2018) - Vander Klok, Jozina; Goad, Heather; Wagner, Michael
Abstract : We compare the use of prosodic prominence in English and French to convey focus. While previous studies have found these languages, and Germanic vs. Romance more generally, to differ in their use of prominence to encode focus (e.g., Ladd 1990 ; 1996 ; 2008 ; Lambrecht 1994 ; Cruttenden 1997 ; 2006 ), exactly what underlies the difference remains an open question. We investigate two possibilities: The difference between the languages could be due to a difference in their phonology, restricting the circumstances in which material can be prosodically reduced, as proposed in Féry (2014 ). Alternatively, there could be syntactic, semantic, and/or pragmatic differences concerning when prominence can be used to encode focus. We compare these hypotheses in a production study which varied the type of focus context (corrective, contrastive, parallelism) to establish the contextual conditions on when a shift in prosodic prominence can occur. The results confirm earlier claims that French uses prosodic prominence to encode focus in corrections, but fails to prosodically encode other types of focus, in contrast to English. We further find that French and English encode focus with very similar acoustic means. Our results show that both languages have the phonological/phonetic means to encode focus using prominence shifts, but differ with respect to the semantic and pragmatic circumstances in which they use them. We propose that these semantic/pragmatic differences between English and French are a result of differences in the syntactic scope possibilities of the focus operator involved in prosodic focus marking.